Labour law protection in cross-border employment - Streithofer, Petra (Momentum Quarterly, 2012)
The aim of this paper is to provide an overview on problems concerning transnational employment contracts involving various levels of regulation. Problems concerning counseling of employees and workers were taken into account. Furthermore, the relevant European Fundamental Freedoms are presented after reviewing the harmonization of employment law within the EU. Also, the principles of conflict of law rules are explained in the context of employment law. Additionally, the controversial jurisdiction of the ECJ concerning minimum standards for the posting of workers is detailed, as well as the debate surrounding the principle of country origin regarding the services directive. Finally, an outlook and proposals leading to enhanced protection of employees and workers are provided.